FROM CHARISMA TO ACADEMIC RATIONALITY: An Ethnographic Study of “Academic Kiai” Leadership in Indonesian Pesantren - Mowafg Masuwd; Yoga Irama; Zayad Abd. Rahman; Moh. Asror Yusuf; Najah Baroud (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2026)
This study explores Kiai Sanuri’s leadership as an “academic kiai” at Pesantren Sholahuddin Surabaya, focusing on how his approach reshapes the cultural foundations of a traditional Islamic boarding school. Employing an ethnographic qualitative design, the research draws on in-depth interviews, participant observation, and institutional documents. The findings show that Kiai Sanuri has cultivated an integrative leadership model that brings together charismatic religious authority, participatory governance, and academically grounded management. Leadership practices are expressed through structured decision-making, strategic planning informed by evidence, and the deliberate integration of scientific literacy into everyday pesantren life. These efforts have strengthened organisational professionalism, expanded educational networks, enhanced academic standards, and repositioned santri as active contributors to knowledge. The study suggests that the “academic kiai” model offers a credible and contextually grounded framework for pesantren leadership in navigating contemporary educational and social change.